Analisis kesalahan ejaan bahasa indonesia pada karangan deskripsi peserta didik kelas V sekolah dasar - Dewi Masithoh; Slamet Slamet; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2023)
This research was conducted with the aim of describing the forms of Indonesian spelling errors and the factors that influence Indonesian spelling errors in descriptive essays for grade V students. This research used a qualitative descriptive research method. The data comes frim the words, sentences, and paragraphs contained in the essay. The data source is student essay. The data analysis technique used is the analysis of language errors Tarigan. The forms of errors found included errors in the use of letters by 52.09%, writing words by 20%, using punctuation by 27%, and writing absorptionelements by 0.09%. Factors that affect spelling errors in student’s descriptive essays include: (1) student’s lack of understanding of spelling, (2) lack of practice and habituation, (3) students have difficulty writing spellings according to the guidelines for using Indonesian spelling. The research implications are divided into practical and theoretical implications.